UPAYA GURU MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA GRAFIS DI MIS LIKI SOLOK SELATAN - Sarifatna, Desven; Zulfamnanna; Seprian Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low level of understanding among sixth-grade students at MIS Liki Solok Selatan in learning Islamic Religious Education (PAI). Students tended to memorize the learning materials without fully understanding the concepts. As a result, when they forgot the memorized content, they were unable to explain the material or answer questions at the end of the lesson. In addition, teachers rarely used learning media, causing the learning process to be dominated by verbal explanations, with students acting as passive recipients. The low level of students’ understanding and learning motivation can be addressed through the use of engaging learning media, one of which is graphic media. The purpose of this study was to improve students’ learning motivation in Islamic Religious Education through the use of graphic media at MIS Liki Solok Selatan. This study employed classroom action research (CAR) involving 13 sixth-grade students, consisting of 9 male students and 4 female students. The research was conducted in two cycles using graphic media, while data were collected through questionnaires and tests. The results of the study indicated an improvement in students’ motivation and learning outcomes in Islamic Religious Education after the implementation of graphic media. This was evidenced by: (1) the average learning outcomes and learning motivation before the use of graphic media were low, with an average learning score of 51.53 and learning motivation score of 44.53, which did not meet the Minimum Mastery Criteria (KKM); (2) the level of learning mastery increased from 51.53 in the pre-cycle stage to 67.30 in cycle I and further increased to 85 in cycle II; (3) students’ learning motivation improved from an average score of 44.53 before the action to 64.23 in cycle I and significantly increased to 84.38 in cycle II. Based on these findings, it can be concluded that the use of graphic media was effective in significantly improving students’ learning motivation and learning outcomes.